Understanding the nexus between water, energy and food in the context of climate change adaptation: a river basin perspective - Dlamini, N.; Senzanje, A.; Taguta, C.; Dirwai, Tinashe Lindel; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
Climate change is a phenomenon that significantly affects vulnerable societies by disrupting water, energy, and food security. Hence, to meet projected socioeconomic needs while ensuring the sustainable development of these resources, a multidisciplinary approach to managing water, energy, food, and the environment under climate change is essential. This chapter outlines and promotes the water-energy-food (WEF) nexus approach, a holistic methodology that is becoming highly prevalent for more effective resource usage and economic growth. Furthermore, in light of climate change adaptation, this chapter discusses what adaptation means in today’s climate-sensitive society and the possible impact on resource security. A basin-level review on climate change impacts on WEF resources in the Buffalo River catchment, KwaZulu-Natal, South Africa, was conducted, which revealed that impacts from water pressures imposed by climate change and incoherent management of water resources are anticipated to have an adverse impact on agricultural production and the energy sector. Findings also emphasize the significance of adapting to the WEF nexus’ systems thinking approach in resource management under climate change, which addresses synergies, trade-offs, and harmonisation of management strategies.